Tourism and Conservation-based Development in the Periphery Lessons from Patagonia for a Rapidly Changing World - Gale-Detrich, Trace; Ednie, Andrea; Bosak, Keith (Natural and Social Sciences of Patagonia, 2023)
This open access book applies a social ecological systems (SES) lens to conservation-based development in Patagonia, bringing together authors with historical, contemporary, and future-oriented perspectives in order to increase understanding of the social and environmental implications of nature-based tourism and other forms of conservation-based territorial development. By focusing on Patagonia (as a region) and its various forms of conservation-based development, this book contributes one of the first collections of South American based lessons and will be valuable to researchers and practitioners, both locally and around the world, seeking to better understand complex interconnections between social and ecological environments, and pursue a similar path to resilience and sustainability.